THE MEDIATING ROLE OF JOB SATISFACTION IN THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND TRANSFORMATIONAL LEADERSHIP ON THE JOB PERFORMANCE - Levira Luciana leonata; Agustiono (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Nowadays, the business competition in Indonesia is becoming very hard, especially in the distribution and food beverage sector. Many companies struggle with human resource problems. One major issue is high turnover, meaning many employees resign from their jobs frequently. This study investigates PT. Kapitan Prima Mandiri, a company currently facing this specific problem. The management aims to understand how to improve employee performance and retention. This research focuses on two main factors: the leadership style of the supervisor (Transformational Leadership) and the emotional skills of the employees (Emotional Intelligence). The objective is to determine if these factors improve Job Performance and to check if Job Satisfaction acts as a "bridge" or mediator in this relationship. The entire population of 89 employees will be surveyed using a questionnaire. The data was analyzed using SmartPLS software. The results indicate that Emotional Intelligence and Transformational Leadership are very important. However, the most significant finding is that these factors work best when they first create employee satisfaction. If employees are satisfied with their job, their performance improves. This suggests the company should focus on creating a positive work environment.